If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18(c + -1) + -18 = 0 Reorder the terms: -18(-1 + c) + -18 = 0 (-1 * -18 + c * -18) + -18 = 0 (18 + -18c) + -18 = 0 Reorder the terms: 18 + -18 + -18c = 0 Combine like terms: 18 + -18 = 0 0 + -18c = 0 -18c = 0 Solving -18c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-18'. c = 0 Simplifying c = 0
| 3(n-4)=-1/2 | | x1/2=-5/12 | | n/1.9=3 | | 4(x/4) | | 45.49-30= | | 10+3x=6x+8 | | 4x-5=-32x+16 | | 3p+5=38 | | x+69=x+121 | | -8(-8+3n)-n=-26+5n | | xy^3*zxy^2=46 | | -2.6-3.4= | | j-0=1.8 | | 9x-21=35-1x | | 2.5*x= | | X+15/18=19/2 | | x/4*4=25*4 | | x/4*4=24*4 | | 14x+7x+12x+420+42x+336=84x | | -3r-8=-5-12 | | -1/2*-6+9 | | 5x=-2x-14 | | -4(2+x)=-12 | | -4-(-2)/-4= | | (5-3i)(8+i)=0 | | 420/15 | | 7x-(2x+1)=7-(x-4) | | 7s=21s-350 | | -18+16= | | 3*x+1=40 | | 3+1/2x=-4 | | 12/5w=13/10 |